ESTIMATION OF THE DURATION OF WORKING HOURS IN NETWORK PLANNING USING PROBABILITY THEORY - Gusmanova, Ф..Р.; Satybaev, А.Д.; Abdulkarimova , Г.; Berkimbaeva, C.Б.; Dalbekova, К.С. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
The article deals with the organization and control of a complex of calculation methods, integrated work planning and management, based on process modeling using network graphics in network planning and management. The main parameters of network graphics are given and a brief description is given. The types of stocks of working time are described. Particular attention was paid to the features of determining the duration and topology of the critical path. Algorithms for planning, creating and configuring network graphics are considered. Finally, the network graphics are analyzed and optimized. It is based on the fact that the level of difficulty in the timely execution of each group of non-critical paths can be determined using the intensity factor of work.Improving the organization of work with deadlines means optimizing network graphics. It is indicated that optimization is carried out in order to reduce the duration of the critical path, equalize the intensity factors, rational use of resources.